Desain dan Analisis Tanki ISO LNG Kapasitas 40 feet Menggunakan Teknik Finite Element Analysis - Freddy Marpaung; Endarto Tri Wibowo; Rudias Harmadi (Fakultas Teknik Universitas Pancasila, 2022)
Development of liquified natural gas (LNG) ISO tank in Indonesia pays significant attention due to this product is still imported and it has high LNG market potential. In addition, this research is in line with national research priorities in the maritime sector to implement energy equality in Indonesia. As a first step in the research, the ISO tank model designed by using CATIA and structural testing using ANSYS software for finite element analysis. This simulation test is carried out to identify areas that receive high stress in the tank shell and the support structure of the tank. In addition, this virtual test was conducted to quantify the stress and safety factor of the ISO tank model. With this simulation, it is hoped that a more efficient and safer ISO tank design that meets existing regulatory standards can be obtained.